EBusiness & eCommerce : Managing the Digital Value Chain / Andreas Meier, Henrik Stormer - Meier, Andreas
This textbook progressively describes all of the elements of the value chain for electronic business and electronic commerce. A process-oriented approach is used to present the electronic business transactions that occur between companies, consumers, and public administration, and these are illustrated with case studies. Along with the organization of digital products and services, special attention is paid to marketing, distribution, and customer relationship care.